EXPLORING HOW E-WOM AND ETHICAL SELF-IDENTITY MEDIATE THE IMPACT OF CONSUMER VALUES ON GREEN LUXURY FASHION PURCHASE INTENTION - Qadri, Rizni Aulia; Serly, Serly; Purwianti , Lily (Jurnal Keuangan dan Bisnis, 2025)
Purpose: This study investigates the effects of environmental, social, functional, and personal values on consumers’ purchase intentions toward luxury fashion, with ethical self-identity and electronic word-of-mouth (e-WOM) serving as mediating variables. Design/Methodology/Approach: A quantitative research design was applied using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected from 468 social media users who expressed interest in luxury fashion consumption. Findings: The results indicate that environmental, social, and functional values positively influence ethical self-identity, while social, functional, and personal values significantly enhance social media engagement. Furthermore, e-WOM mediates the relationship between social value and purchase intention, suggesting that perceived social recognition is transformed into online advocacy, which ultimately strengthens consumers’ willingness to purchase sustainable luxury fashion. Practical Implications: These findings offer insights into how consumer value perceptions and online interactions jointly shape purchase intentions within the sustainable luxury context. The results may guide brand managers in developing strategies that integrate sustainability communication and consumer engagement through digital platforms. Originality/Value: This study contributes to sustainable luxury research by integrating two mediating mechanisms ethical self-identity and e-WOM into a single structural framework. Unlike prior studies that examined luxury values independently or without behavioral linkages, this research elucidates how value perceptions are transmitted through ethical self-definition and digital advocacy before influencing purchase intentions, thereby offering a more holistic understanding of sustainable luxury consumption dynamics.